2016
DOI: 10.1186/s13195-015-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

An integrative genome-wide transcriptome reveals that candesartan is neuroprotective and a candidate therapeutic for Alzheimer’s disease

Abstract: Background: Alzheimer's disease is the most frequent age-related dementia, and is currently without treatment. To identify possible targets for early therapeutic intervention we focused on glutamate excitotoxicity, a major early pathogenic factor, and the effects of candesartan, an angiotensin receptor blocker of neuroprotective efficacy in cell cultures and rodent models of Alzheimer's disease. The overall goal of the study was to determine whether gene analysis of drug effects in a primary neuronal culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 112 publications
5
25
0
Order By: Relevance
“…We mined published microarray data sets to further define phenotypes in the present data using Gene Set Enrichment Analysis (GSEA) 87 ( http://broadinstitute.org/GSEA ) according to methods described previously 88 . The GSEA algorithm computes a ranked list of all genes from a microarray comparison between two conditions and identifies whether individual members of an a priori functionally defined gene set (black vertical bars) are enriched at either the top (red area) or bottom of the ranked genes (blue area) or randomly distributed across the whole ranked gene list, using a modified Kolmogorov-Smirnov statistic and generating an enrichment score.…”
Section: Methodsmentioning
confidence: 99%
“…We mined published microarray data sets to further define phenotypes in the present data using Gene Set Enrichment Analysis (GSEA) 87 ( http://broadinstitute.org/GSEA ) according to methods described previously 88 . The GSEA algorithm computes a ranked list of all genes from a microarray comparison between two conditions and identifies whether individual members of an a priori functionally defined gene set (black vertical bars) are enriched at either the top (red area) or bottom of the ranked genes (blue area) or randomly distributed across the whole ranked gene list, using a modified Kolmogorov-Smirnov statistic and generating an enrichment score.…”
Section: Methodsmentioning
confidence: 99%
“…In PD mouse model, ARB treatment protected from dopaminergic neurons death, reduced motor deficits, and inhibited microglial activation . Candesartan (a blood‐brain barrier–entering ARB) reversed the neurotoxic effects of AT1R overstimulation in animal models of systemic inflammation . Candesartan, subcutaneous administered, to LPS‐injected hypertensive or normotensive rats decreased the LPS‐induced gliosis in the brain parenchyma .…”
Section: Introductionmentioning
confidence: 99%
“…Candesartan, subcutaneous administered, to LPS‐injected hypertensive or normotensive rats decreased the LPS‐induced gliosis in the brain parenchyma . Interestingly, a recent study indicated a great neuroprotective potential for candesartan in AD as it affected the expression of hundreds of genes in AD patients’ cortex and hippocampus …”
Section: Introductionmentioning
confidence: 99%
“…These findings resulted in considerable advances in utilizing brain RAS blockade or RAS modulation as a therapeutic strategy to treat diseases beyond neurogenic hypertension. This is specifically relevant in stroke and cerebrovascular diseases, Alzheimer's disease, cognitive dysfunction, Parkinson disease, aging, and others [107][108][109][110][111][112][113][114][115]. Numerous other new molecules or administration routes to target the brain RAS are currently under investigation.…”
Section: Novel Drugs To Modulate the Brain Ras And Potential New Clinmentioning
confidence: 99%